The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app11010291
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Design of OTA-Based Gyrator Realizing Fractional-Order Inductance Simulator: A Comprehensive Analysis

Abstract: A detailed analysis of an operational transconductance amplifier based gyrator implementing a fractional-order inductance simulator is presented. The influence of active element non-ideal properties on the gyrator operation is investigated and demonstrated by admittance characteristics and formulas for important values and cut-off frequencies in these characteristics. Recommendations to optimize the performance of the gyrator in terms of operation bandwidth, the range of obtainable admittance magnitude, and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Unfortunately, the obtainment of C eq is not discussed as well as details about adjustability and tunability. Kubanek et al [48] analyzed the features of CPE usage in a standard loop of two transconductors-based gyrator including real properties of the active devices [5]. All consequences of parasitic properties of active devices are important for a correct selection of values of elements and precise results as well as a design guide [48].…”
Section: Discussion Of Recent Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the obtainment of C eq is not discussed as well as details about adjustability and tunability. Kubanek et al [48] analyzed the features of CPE usage in a standard loop of two transconductors-based gyrator including real properties of the active devices [5]. All consequences of parasitic properties of active devices are important for a correct selection of values of elements and precise results as well as a design guide [48].…”
Section: Discussion Of Recent Developmentmentioning
confidence: 99%
“…Kubanek et al [48] analyzed the features of CPE usage in a standard loop of two transconductors-based gyrator including real properties of the active devices [5]. All consequences of parasitic properties of active devices are important for a correct selection of values of elements and precise results as well as a design guide [48]. Authors of [26] (included in comparison with integer-order solutions in Table I) have shown a very simple topology utilizing a single commercially available active device including several integrated subparts (current conveyors, adjustable current amplifier, current feedback operational amplifier [1], [2]).…”
Section: Discussion Of Recent Developmentmentioning
confidence: 99%
“…and the expressions of the magnitude frequency response and the half-power frequency are given in ( 9) and (10), respectively.…”
Section: Power-law Filtersmentioning
confidence: 99%
“…Non-integer order signal processing has received significant research interest in the following fields [1][2][3][4][5][6]. The first field is electrical engineering, for implementing filters and oscillators [5,[7][8][9][10][11][12][13][14][15], chaotic systems [16], sensor systems [17], and control systems [2,[18][19][20][21]. This originates from the fact that both filters and oscillators offer additional degrees of freedom due to the non-integer order, which opens the door for scaling the characteristic frequencies of the filters/oscillators, as well as for precisely controlling the gradient of the transition from the pass-band to the stop-band.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage is that the electronic control of the order is not available (the values of resistors and capacitors of the RC structure vary based on the desired FO and thus the resistors and capacitors of the RC structure need to be changed, or whole RC structure has to be redesigned and replaced). The last common technique is using emulators exhibiting specific behavior of FOE [35][36][37][38][39]. The structure of these emulators is usually more complex and require active elements in comparison to the previous approaches nonetheless, they often offer the electronic control of some parameter (fractional order, frequency band where the FO approximation is valid, gain adjustment, etc.…”
Section: Introductionmentioning
confidence: 99%